2021
DOI: 10.1186/s12872-021-02346-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic shock with highly complicated course after influenza A virus infection treated with vva-ECMO and Impella CP (ECMELLA): a case report

Abstract: Background The value of mechanical circulatory support (MCS) in cardiogenic shock, especially the combination of the ECMELLA approach (Impella combined with ECMO), remains controversial. Case presentation A previously healthy 33-year-old female patient was submitted to a local emergency department with a flu-like infection and febrile temperatures up to 39 °C. The patient was tested positive for type-A influenza, however negative for SARS-CoV-2. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…Circulatory support consisted of inotropes/vasopressors (used in 58.7% of the cases) and MCS, including extracorporeal membrane oxygenation (ECMO), in 18 cases (24%), intra-aortic balloon pump (IABP) in 9 (12%), and ventricular assist device (VAD) in 7 cases (9.3%). VAD devices used were Impella in four cases [ 20 , 25 , 34 , 60 ], Bi-VAD in two, and catheter-based VAD in one case [ 18 , 50 , 68 ]. Only 1 out of 17 patients with isolated pericarditis required inotropic/vasopressor support compared to 44 out of 58 myopericarditis cases ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation